2012
DOI: 10.1021/bm2016338
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Degradable Polyelectrolyte Multilayers Fabricated Using DNA and a Fluorescently-Labeled Poly(β-amino ester): Shedding Light on the Role of the Cationic Polymer in Promoting Surface-Mediated Gene Delivery

Abstract: Polyelectrolyte multilayers (PEMs) fabricated from cationic polymers and DNA have been investigated broadly as materials for surface-mediated DNA delivery. One attractive aspect of this `multilayered' approach is the potential to exploit the presence of cationic polymer `layers' in these films to deliver DNA to cells more effectively. Past studies demonstrate that these films can promote transgene expression in vitro and in vivo, but significant questions remain regarding roles that the cationic polymers could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 71 publications
4
40
2
Order By: Relevance
“…Our system has higher transfection efficiency than those reported substrate-mediated gene delivery systems in MSCs, whose transfection efficiency ranges from ~5% to ~40%. 3,5,12,15 But because of the different experimental conditions, including the quality of plasmid DNA, cell types, cell seeding density, and characterization methods, …”
Section: Transfection In Mscs In Vitromentioning
confidence: 99%
See 3 more Smart Citations
“…Our system has higher transfection efficiency than those reported substrate-mediated gene delivery systems in MSCs, whose transfection efficiency ranges from ~5% to ~40%. 3,5,12,15 But because of the different experimental conditions, including the quality of plasmid DNA, cell types, cell seeding density, and characterization methods, …”
Section: Transfection In Mscs In Vitromentioning
confidence: 99%
“…In this therapeutic strategy, plasmid deoxyribonucleic acid (pDNA) is first immobilized onto a biomaterial surface and then released in a controlled and sustained manner to transfect cells surrounding materials. [1][2][3][4][5][6][7] As compared with the conventional bolus nonviral gene delivery, where cells are transfected by the suspended pDNA/vector complexes in liquid, substrate-mediated gene delivery has many advantages. The first one is its controllability, where gene transfection can be designed to meet clinical needs through controlling the amount of immobilized pDNA and its subsequent release from the substrate surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic agents to be released are incorporated during multilayer assembly and are subsequently released either via simple diffusion [32], biodegradation of the polyelectrolyte building block [33], or induced by internal [34] or external [35] triggers. In view of cell transfecting surfaces, Lynn and Bechler reported that the two multilayer components (i.e., hydrolysable poly(b-amino ester) and DNA) were found to co-localize within transfected cells cultured in the vicinity of the surface, indicating that either the polymer-DNA complex is released, or the separate components are released and later form a complex in cell culture medium before being internalized by cells [36].…”
Section: Introductionmentioning
confidence: 99%